Metabolic and performance responses to a simulated routine in elite artistic swimmers - Bentley, D. J.; Viana, E.; Logan-Sprenger, H. M. (Sports, 2022)
The purpose of this investigation was to examine the interrelationship between time spent underwater (UW), movement frequency and accompanying blood acid base balance response. Elite artistic swimmers (n = 6) participated in the investigation and were all familiar with the testing procedures. All athletes completed the same choreographed artistic swimming routine. The routine was videoed and the number of movements during each `lap` of the routine counted. Fingertip capillary blood samples were collected prior to the routine 60 sec post routine for pH, partial pressure of carbon dioxide (pCO2), partial pressure of oxygen (pO2), bicarbonate (HCO3-) and potassium (K+). and lactate (La) concentration (mmol/L). On a separate day an incremental exercise test to exhaustion was performed on a cycle ergometer for determination of maximal oxygen uptake (VO2max). Over half the routine was performed underwater (56 ± 4%). Aside from pCO2 (-1.07 ± 12.29%, p = 0.686), there were significant changes in all variables measured from the BG analysis. VO2peak was significantly correlated to total UW of the routine (r = -0.93; p = 0.007). as well as ?PO2 r = 0.47 and ?HCO3 r = 0.51. There was also a significant correlation between total UW and post routine pCO2 (r = 0.86; p = 0.030). There was also a significant correlation between total movements during the routine and post pO2 (r = -0.83; p = 0.044). These data show UW in combination with movement rate during a AS routine imfluence the metabolic response to the exercise. In addition, VO2max represents an important performance variable influencing AS performance.